Descriptions of two new and one newly recorded enchytraeid species (Clitellata, Enchytraeidae) from the Ozegahara Mire, a heavy snowfall highmoor in Central Japan - Torii, Takaaki (Zootaxa, 2015)
Three species of semi-aquatic freshwater Enchytraeidae of the genera Mesenchytraeus Eisen, 1878, Chamaedrilus Friend, 1913 and Globulidrilus Christensen & Dózsa-Farkas, 2012 are described from stream, wet soil or snow habitats in the Ozegahara Mire, an extensive high moor in heavy snowfall area in central Japan. Among Mesenchytraeus speies, Mesenchytraeus nivalis sp. nov. is distinguished by not having enlarged chaetae and spermathecal diverticula, vas deferens with atrial glands 3 or 4 in number and club-shaped, spermathecal ental duct short, with sperm bundles in the sperm sack. Chamaedrilus ozensis sp. nov. closely resembles C. floridae, but the length of the sperm funnel and character of the coelomocytes are different. Globulidrilus helgei Christensen & Dózsa-Farkas, 2012 is recorded for the first time from Japan.